The best interests test at the end of life on PICU: a plea for a family centred approach. Issue 3 (11th October 2007) - Inwald, D
Abstract : Approximately 80% of deaths in paediatric intensive care units occur as a result of a decision for limitation or withdrawal of life sustaining treatment, which in English law must be made with reference to the best interests of the child. However, as factors included in the best interests assessment depend on the subjective view of the decision maker, the test is not objective. Furthermore, the test is individualistic, in that only the child's interests are considered, ignoring the interests of others. Additionally, there is an element of absurdity as only those who are alive can be said to possess interests and any decision resulting in death will result in loss of all interests along with loss of life. These criticisms could be largely addressed by taking into account the interests of others, particularly the interests of close family members.